2023
DOI: 10.7150/ijbs.85158
|View full text |Cite
|
Sign up to set email alerts
|

IκB kinase β (IKKβ): Structure, transduction mechanism, biological function, and discovery of its inhibitors

Abstract: The effective approach to discover innovative drugs will ask natural products for answers because of their complex and changeable structures and multiple biological activities. Inhibitory kappa B kinase beta (IKKβ), known as IKK2, is a key regulatory kinase responsible for the activation of NF-κB through its phosphorylation at Ser177 and Ser181 to promote the phosphorylation of inhibitors of kappa B (IκBs), triggering their ubiquitination and degradation to active the nuclear factor kappa-B (NF-κB) cascade. Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 188 publications
0
7
0
Order By: Relevance
“…Alantolactone was also shown to inhibit IκB kinase β by interacting with the ATP-binding site [29]. Since IκB kinase β plays an essential role in the NF-κB signaling pathway [24], IκB kinase β may be a common target protein of alantolactone in the NF-κB signaling pathway. In the present study, we found that TNF-R1 was down-regulated in A549 cells when they were exposed to alantolactone for 1 h. In contrast, alantolactone did not reduce the expression of TRADD, RIPK1, or TRAF2, which are adaptor proteins that are part of the TNF-R1 complex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alantolactone was also shown to inhibit IκB kinase β by interacting with the ATP-binding site [29]. Since IκB kinase β plays an essential role in the NF-κB signaling pathway [24], IκB kinase β may be a common target protein of alantolactone in the NF-κB signaling pathway. In the present study, we found that TNF-R1 was down-regulated in A549 cells when they were exposed to alantolactone for 1 h. In contrast, alantolactone did not reduce the expression of TRADD, RIPK1, or TRAF2, which are adaptor proteins that are part of the TNF-R1 complex.…”
Section: Discussionmentioning
confidence: 99%
“…An α-methylene-γ-lactone moiety reacts with the thiol groups of proteins via the Michael addition reaction [22][23][24]. To clarify whether the α-methylene-γ-lactone moiety of alantolactone is critical for down-regulating the expression of TNF-R1, A549 cells were pretreated with glutathione, NAC, and L-cysteine, all of which contain a thiol group, and were then treated with alantolactone.…”
Section: The Down-regulation Of Tnf-r1 Expression By Alantolactone Wa...mentioning
confidence: 99%
See 1 more Smart Citation
“…pursuit of therapies for inflammatory, autoimmune, respiratory, and oncological conditions [40][41][42][43]. In an AD APP-transgenic murine model, IKKβ inhibition proved to be effective in reducing inflammatory microglial activation and decreasing TNF-α, Il-1β, and iNOS inflammatory gene transcription caused by Aβ deposits, thereby improving cognitive functions [44,45].…”
Section: Designmentioning
confidence: 99%
“…Subsequently, the released dimer translocates to the nucleus, where it regulates the gene expression of multiple inflammatory pathways [ 39 ]. The inhibition of IKKβ (also known as IKK2), with the aim of disrupting the activation of NF-κB, has garnered significant attention in the pursuit of therapies for inflammatory, autoimmune, respiratory, and oncological conditions [ 40 , 41 , 42 , 43 ]. In an AD APP-transgenic murine model, IKKβ inhibition proved to be effective in reducing inflammatory microglial activation and decreasing TNF-α, Il-1β, and iNOS inflammatory gene transcription caused by Aβ deposits, thereby improving cognitive functions [ 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%